Mikhail Katkov, Publisher of Fyodor Dostoevsky - Nikolay N. Podosokorsky (Достоевский и мировая культура: Филологический журнал, 2024)
The review is devoted to the monograph by Professor Susan Fusso of Wesleyan University Editing Turgenev, Dostoevsky, and Tolstoy. Mikhail Katkov and the Great Russian Novel, published in 2023 in Russian for the series “Modern Western Russian Studies” (the book was published in the original language in 2017). Fusso’s work reveals and clarifies various aspects of the biography of the charismatic editor of the magazine Russkii Vestnik Mikhail Katkov (1817–1887) and contains valuable observations regarding his difficult personal and working relationship with Fyodor Dostoevsky, whose four great novels (Crime and Punishment, The Idiot, Demons, and The Brothers Karamazov) were first published by Katkov.